Male sexuality under surveillance : the office in American literature - Thompson, Graham, 1965- (University of Iowa Press, 2003)
Male Sexuality under Surveillance is a lively, intelligent, and expertly argued analysis of the construction of male sexuality in the business office. Graham Thompson interweaves three main threads: a historicized cultural analysis of the development of the modern business office from its beginnings in the early nineteenth century to the present day, a Foucauldian discussion of the office as the site of various disciplinary practices, and a queer-theoretical discussion of the textualization of the gay male body as a device for producing a taxonomy of male-male relations. The combination of the.